Learning Achievement Analysis of Male and Female Students at the PPNS and Polmed to Meet the Global Challenges - Sandora, Rina; Syahdewa, Budi Indra (UNIPA PRESS, 2020)
Industry revolution 4.0 era provides opportunities as well as threats for the students and alumni graduated from vocational education. Man roles are gradually taken by automatic machines. Consequently, unemployment is increasing. This certainly will contribute to the either local or national problems. Therefore, vocational education students have to intensify their learning achievements. This study discusses the learning achievements of the male and female students at the Shipbuiding Institute of Polytechnic Surabaya (PPNS) and Medan State Polytechnic (Polmed). The analysis of learning achievements in this study used the documentation data of the GPA in scale 4, taking the whole population either male (M) or female (F) in the academic year 2015/2016, 2016/2017, and 2017/2018. In the last three years, total PPNS’s graduates are 1959 (1418 male, 541 female) and Polmed’s are 5938 (2821 male, 3117 female). Based on the descriptive quantitative analysis, the average of learning achievements at PPNS shows that accumulated GPA of the female students’ is 3.39 > male students’ 3.28. While at Polmed, it is GPA of female students’ is 3.27 > male students’ 3.14. Total of students is still gender imbalance referring to the graduates data in year 2018 for PPNS’ Welding Study Program in which having only two female students with average GPA 3.41 and 53 students with average GPA 3.15, meanwhile at Polmed, the total students with largest gap in gender occured at the Mechanical Engineering Study Program with total of male students 240 (average GPA 3.10) and female students only 11 (average GPA 3.20). This result indicates that in these two vocational educational institutions, e.i. PPNS and Polmed, the learning achievement of female students is betterand more competitivable than the other